Public Budgeting in The Fiscal Decentralization Policy in Indonesia - Dyah Mutiarin (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2017)
Public budgeting in the context of fiscal decentralization has many problems in Indonesia. The problems can be traced from its contributions to the development such as budget effectiveness, budget impact, budget efficiency, facing big corruption, and also on poverty reduction becomes a serious problem that must be resolved by the Government of Indonesia.  In the area of implementation, public hope that the National and Local budget can improve the welfare of society as a whole. In terms of spending, national spending quality has declined. The budget itself absorbs big portions budget for the personnel expenditure, while capital expenditure is very much limited. Personnel expenditure, capital expenditure, and Social expenditure reflect the Government understanding of the needs of the public at large.  From the perspective of budget policy, public expenditure in Indonesia has still weak in reflected the public needs. There are many interests to intervene budget process and configuration both politically and bureaucratically. The budget policy was not in line with democratic principles that public policy must be based on public consent. When it comes to public consent then should the public budget to accommodate the public interest-oriented public service for the welfare of the public.